HUBUNGAN MENOPAUSE DENGAN TIMBULNYA GANGGUAN DEPRESI DAN KECEMASAN DI PIMPINAN DAERAH AISYIYAH KOTA MEDAN - AZRI A; SINAGA R (LP2MTBM MAKARIOZ, 2019)
Menopause is defined as permanent cessation of menstruation due to loss of ovarian follicular activity due to aging manifested for 12 months consecutive amenorrhoea. Menopausal events have many impacts on the physical and psychological changes of a person, physical changes in menopause can have an impact on the onset of menopausal disease in terms of physical and psychological. Psychic complaints of menopause are more influential on quality of life compared with the physical complaints experienced menopause. The most frequent psychic complaints are anxiety and depression in menopausal women whose very individual nature is influenced by socio-cultural, educational, environmental, and economic. Method: This research was conducted descriptive analytic with a cross-sectional design which is a form of non-experimental study with the measurement of variables performed simultaneously at one time. Results:From the results of the study showed that menopausal women experience more depression and anxiety than women who have not yet menopause. Conclusion: There is a relationship of menopause to depression and anxiety.